Folate Reverses NF-κB p65/Rela/IL-6 Level Induced by Hyperhomocysteinemia in Spontaneously Hypertensive Rats - Zhang, Lihua; Li, Zhongliang; Xing, Changcheng; Gao, Ning; Xu, Rui (Frontiers in Pharmacology, 2021)
Hypertension combined with hyperhomocysteinemia (HHcy) is correlated with a high risk of cardiovascular diseases (CVD). HHcy arises from abnormal homocysteine (Hcy) metabolism and is also regarded as a metabolic-related disease. However, the mechanism of HHcy aggravating hypertensive arterial damage and the efficacy of folate (FA) as a beneficial supplement have not been fully elucidated. In this study, we established an rat HHcy model and an hypertension combined with HHcy model. Rat tail artery blood pressure (BP), plasma Hcy, serum superoxide dismutase (SOD) and malondialdehyde (MDA) were measured. Rat thoracic aorta was harvested for pathological analysis after 12 weeks of the experiment. Rat relative expression levels of oxidative stress and immune/inflammation in arterial tissues were detected by quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting. The results demonstrated that the relative expression levels of oxidative stress and immune/inflammation were the highest in the HHcy + SHR group, followed by the SHR group. HHcy significantly up-regulated the levels of interleukin-6 (IL-6) and nuclear factor-κ-gene binding (NF-κB) p65/Rela in the arterial tissue of hypertension rats, while folate significantly inhibited the two immune/inflammatory genes expression. Folate significantly increased the level of SOD and reduced the level of MDA in the blood. Additionally, the serum level of HHcy was markedly decreased following FA treatments. In conclusion, HHcy-induced immune/inflammatory response aggravated the arterial damage in hypertension rats. Furthermore, folate exhibited anti-inflammatory and antioxidant pharmacology and could serve as an effective therapeutic agent against hypertension combined with HHcy, through inhibiting the NF-κB p65/Rela / IL-6 signalling pathway and significantly increasing the SOD activity pathway.